Analisis Jual Beli Online Sistem Dropshipping Pada Toko Pakaian di Kota Kendari Ditinjau Dari Etika Bisnis Islam - Sinarwaty Daswan; Lestari Daswan (STAI DDI Pinrang, 2026)
This study aims to identify and understand the types of transactions involved in online sales using the dropshipping system at clothing stores in Kendari City. This study also aims to determine online buying and selling using the dropshipping system in terms of Islamic business ethics in clothing stores in Kendari City. This study uses a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation of dropshipping practitioners and consumers who are directly involved. Informants were selected using purposive sampling, with a total of 13 informants. The results show that dropshipping practices in clothing stores in Kendari City, when viewed in terms of transaction processes, transaction types, and contract clarity, have mostly applied Islamic business ethics principles such as honesty, transparency, responsibility, and fairness. However, practices that contradict sharia principles were still found, such as excessive promotion, concealment of supplier identity, and discrepancies between the goods received by consumers and the information promoted. In terms of contracts, most transactions used salam contracts, in which the dropshipper acted as a marketing intermediary for the supplier's products